2018
DOI: 10.5688/ajpe6636
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Teaching Methods on Skin Disorders Using Standardized Patients Dressed in Moulage vs Paper Cases

Abstract: Objective. To determine whether using standardized patients dressed in moulage improves pharmacy students' ability to assess skin disorders compared to using picture-based paper cases. To determine pharmacy student preferences when learning assessment of skin disorders through these two educational methods. Methods. Faculty members investigated student assessments of drug-induced skin disorders and contact dermatitis by using picture-based paper cases compared with using standardized patients dressed in moulag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…It seemed that the moulages used in our study activated the students' visual sense and allowed the students to identify and classify pressure injuries. In a study by Flores and Hess (2018), using SPs dressed in moulage did not improve pharmacy students' visual ability to assess skin disorders compared to using picture-based paper cases. However, students preferred SPs dressed in moulage only when learning the assessment of skin disorders.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It seemed that the moulages used in our study activated the students' visual sense and allowed the students to identify and classify pressure injuries. In a study by Flores and Hess (2018), using SPs dressed in moulage did not improve pharmacy students' visual ability to assess skin disorders compared to using picture-based paper cases. However, students preferred SPs dressed in moulage only when learning the assessment of skin disorders.…”
Section: Discussionmentioning
confidence: 87%
“…(Uzelli Yilmaz & Sari 2018; Stokes-Parish, Duvivier & Jolly 2019; Sarmasoglu et al 2020). Several studies have been published on the evaluation of skin assessment skills among healthcare students (Seckman & Ahearn 2010;Goulart et al 2012;Hernandez et al 2013;Wang et al 2015;Flores & Hess 2018;Zorn, Snyder & Guthrie 2018;Uzelli Yilmaz & Sari 2021). Sezgunsoy and Basak (2020) investigated whether using moulage on high-fidelity simulators improves nursing students' clinical skills to assess PI compared to using visuals.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Neither of above-mentioned studies showed statistically significant differences in students' scores at Kirkpatrick's Level 2. 33,34 In another study, however, Gillette et al 17 observed improved students' assessment results when they were taught with SP when compared with students taught using peer role-play or other active learning methods. Additionally, in the discussion they pointed out some generalizability issues of previously mentioned papers, including small sample size, short intervention period or assessment of only one aspect of communication.…”
Section: Effectiveness Of Sp-methodsmentioning
confidence: 98%
“…peer role-play), results of studies conducted so far are mixed, with different studies indicating superiority, equality and one even inferiority of the SP-method. 17 33 observed that students were more satisfied when drug-induced skin disorders were taught employing a standardized patient dressed in moulage instead of using picture paper cases. This observation is very close to the results of Grice et al 34 who compared pharmacy students' satisfaction on teaching physical examination using standardized patients versus manikins.…”
Section: Effectiveness Of Sp-methodsmentioning
confidence: 99%
“…Moulage is the art of applying makeup, tattoos, or other substances to simulate wounds and lesions for teaching purposes (Zorn et al, 2018). Students report that they learn more from moulage-based activities and prefer them over paper-based dermatologic cases (Flores & Hess, 2018). Furthermore, working in teams during moulage-based simulations improves student learning outcomes in areas including communication skills, application of course content, and collaborative clinical decision-making (Della Ratta, 2015; El-Banna et al, 2020).…”
mentioning
confidence: 99%